Marcel Duchamp. - Breton, André; Schwarz, Arturo (Antwerpen : Galerie Ronny Van de Velde, 1991)
Luxe editie van de catalogus van de Marcel Duchamp-expositie in Ronny Van de Velde, Antwerpen; September 15-December 15, 1991. Volledige inhoud volgens het colofon: A portfolio with faithful reproductions of works by Duchamp, also including a copy of H. Vuibert, Les anaglyphes géométriques, Paris, Librairie Vuibert, 1912 (with 3D-glasses) and a reproduction of a page from The Blind Man No. 2 (P.B.T.); a book with articles on Duchamp by André Breton and Arturo Schwarz (inserted, on a seperate sheet, a reproduction of Le Grand Verre); an audiocassette of Duchamp speaking; a single photograph of "Marcel Duchamp at the age Eighty-Five" for View's special Marcel Duchamp number; this very colophon. All these items are packed in a wooden box, the top and bottom of which being reproductions of Duchamp's ' mental' Chess Board."
Cataloog (34 x 24 cm), geb. [22 p.]
Engels
kunstcatalogus
Keywords: Duchamp, Marcel